Wat is kultuur? 'n Filosofiese antwoord - Kirsten, J. M. (Koers, 1984)
The essay offers a philosophical answer to the traditional question concerning the "essence" of culture. A descriptive procedure is adopted whereby the phenomenon of culture is approached from two different, but interrelated perspectives. First of all a cross section is made of the structure of culture in order to describe the phenomenon in its unity. From this dioramic perspective culture is defined as the transcendence of nature by man on the basis of strategic actions which subject both nature and man himself to new and never-changing forms. Secondly an overview is given of the context of culture in order to describe it in its totality. From a panoramic viewpoint, it is suggested, culture refers to history as the encompassing context in which dwelling man moves towards the world of the future through the continuous re-working of his present abode.